Respuestas musculares de la asociación de estatina y ejercicio físico aeróbico en ratas - Bonfim, Mariana Rotta [UNESP]; Camargo Filho, José Carlos Silva [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Padulla, Susimary Aparecida Trevizan [UNESP]; Accioly, Marilita Falângola; Souza, Dorotéia Rossi Silva; Azoubel, Reinaldo (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
Physical exercise and statins, which are recommended for the treatment of dyslipidemia, are independently associated to the occurrence of muscle injury. The objective is analyze the effect of aerobic exercise associated to the use of simvastatin on the morphology of the gastrocnemius muscle. Thirty Wistar rats were divided into six groups, two of which received a standard diet (1 sedentary and 1 exercised) and four (1 sedentary with medication, 1 sedentary without medication, 1 exercised with medication, 1 exercised without medication) received a hypercholesterolemic diet (standard diet with the addition of cholesterol and coconut oil). Simvastatin (20 mg/Kg) was administered five days a week for eight weeks, together with aerobic training on a treadmill (9.75 m/min) for 60 minutes a day. The gastrocnemius muscle was removed, sliced, stained with Hematoxylin-Eosin and submitted to a histochemical reaction to determine mitochondrial activity. The data were analyzed using a paired t-test, analysis of variance and Scheffé's post hoc test (p<0.05). Greater histological alterations were found in the medicated and exercised animals, with a greater frequency of occurrence as well. The histochemical analysis revealed that the medicated groups had fibers with more intensive mitochondrial activity alongside fibers with an absence of reaction. The morphometric analysis revealed no significant differences between groups. It is suggested that simvastatin is a medication that leads to the occurrence of muscle injury and its administration in association with physical activity may exacerbate these injuries. This finding may be related to cellular respiration.
Muscle response to the association of statin and physical exercise in rats
Keywords: Exercise; Hydroxymethylglutaryl-coa reductase inhibitors; Skeletal muscle